Timing of Velopharyngeal Movement during Speech Analyses by NPF-Video Recording System - Sugai, Toshiro (Journal of Japanese Cleft Palate Association, 1985)
Nasopharyngeal fiberscope (NPF) coupled with video recording system was utilized to analyze the timing of velopharyngeal movement during speech. The timing of velopharyngeal closure (TC)and timing of maximum velopharyngeal movement (TM) were determined based on the time of speaking or articulatory release. The participants were 20 normal subjects speaking Kansai dialect Japanese and 20 patients with spatial velopharyngeal incompetence. A superior based pharyngeal flap operation (Unified velopharyngeal plasty) as given to the 20 patients by one surgeon, and differences of velopharyngeal movement timing among pre and post surgical conditions in those patients were also investigated. The present stu d y indicated the following results. 1. The normal subjects demonstrated that the closure and maximum movement of the velopharynx were provided with programmed timing which was appropriate to the sound produ c ed. 2. The twenty patients with VPI presurgically showed several types of temporal controls of the velopharyngeal movement different from the timing of the normals. TC was not measure d because of lack of complete closure. The patients were grouped into three categories b ased on TM measurement. Group A (6 patients) showed statistically similar TM of vowels to those o f the normals and indicated the temporal difference of TM between vowels and consonant /P/. Group B (4 patients) showed only statistical coincidence of vowel TM with those of the normals. Group C (10 patients) showed no statistical similarity of temporal control of velopharyngeal movement with those of the normals. 3. The ten patients categorized i nto Group A and B with similar vowel TM to those of the normals showed remarkable improvement of the velopharyngeal closure in both timing and spatial closing mechanism. The post-surgical measurement of TC statistically coincided with th o se of the normals. Intelligibility of the sound also improved. To the contrary, the patients categorized into Group C showed no improvement of temporal control of the velopharyngeal c losure nor sound intelligibility, though several patients achieved complete velopharyngeal closure after t he pharyngeal flap surgery. 4. The present data indicated that the knowledge concerning the vowel TM provided prognostic evaluation of velopharyngeal incompetence for pharyngeal flap surgery.